Проблемы физического воспитания студенческой молодежи в современной среде - Кац, Н.А.; Ким, В.А.; Козлова, Л.И. (My University, 2013)
This article describes the problems of physical education of students, methodical principles of physical education, methods and forms of influence to the consciousness of young people, issues of methodology and conceptual support of university sport.